Tecnologias Ch'ixi: experiências micropolíticas para descolonizar as tecnologias - o caso da Casa de Cultura Tainã e a Rede Mocambos - Fellner, Ana Maria Rivera (2020)
This doctoral thesis discusses the interaction role of ancestral and digital technologies in two concrete experiences, the Casa de Cultura Tainã and Rede Mocambos to recognize the trajectories effects on decolonizing, organizational, communicative and memory practices. This doctoral thesis seeks to understand the discernment and practices weave by Tainã and Rede and thus expand the discussion on technologies role in subalternized contexts. This knowledge, conceptions, usage practices, appropriation and technologies integration by excluded people have a lot to contribute with the theoretical conceptions develop in the academy and with practical initiatives that aim to make other organizations. In order to understand this community construct this research is based on the anticolonial perspective of participatory action and life stories, that are methods anchored in ethical-political and epistemological principles that allow proximity strategies to be of proximity, alterity and dialogically critical to apprehend from communities’ experience. Therefore a perspective of decolonizing technologies that seeks to understand technologies in its sense of autonomy enables, freedom, communities self-determination, critical awareness, humanity heritage and recognition of the Ch’ixi condition.